Solvothermal preparation of nano-sized CaWO4 particles - Sulawan Kaowphong (2018)
CaWO4 was prepared by solvothermal reaction of Na 2WO4.2H2O and calcium salts (CaCl 2.2H2O, Ca(NO3)2.4H2O and Ca(CH3COO)2) in solvent containing a variety of glycerol/water ratios at 160 °C for 6 h. By using XRD, SEM, TEM and ED, the products compose of nano-sized CaWO4 particles with scheelite structure but different morphologies. Interplanar spaces between (101) planes were determined from HRTEM image, ED patterns and XRD spectra are 0.424, 0.474 and 0.476 nm, respectively. Luminescent intensities of the products prepared in pure water are the highest and their central peaks are the same at 444 nm. In addition, Ca, W and O were detected using EDX.